Overexpression of a novel peanut NBS‐LRR gene AhRRS5 enhances disease resistance to Ralstonia solanacearum in tobacco. Issue 1 (26th July 2016) - Zhang, Chong; Chen, Hua; Cai, Tiecheng; Deng, Ye; Zhuang, Ruirong; Zhang, Ning; Zeng, Yuanhuan; Zheng, Yixiong; Tang, Ronghua; Pan, Ronglong; Zhuang, Weijian
Summary: Bacterial wilt caused by Ralstonia solanacearum is a ruinous soilborne disease affecting more than 450 plant species. Efficient control methods for this disease remain unavailable to date. This study characterized a novel nucleotide‐binding site‐leucine‐rich repeat resistance gene AhRRS5 from peanut, which was up‐regulated in both resistant and susceptible peanut cultivars in response to R. solanacearum . The product of AhRRS5 was localized in the nucleus. Furthermore, treatment with phytohormones such as salicylic acid (SA), abscisic acid (ABA), methyl jasmonate (MeJA) and ethephon (ET) increased the transcript level of AhRRS5 with diverse responses between resistant and susceptible peanuts. Abiotic stresses such as drought and cold conditions also changed AhRRS5 expression. Moreover, transient overexpression induced hypersensitive response in Nicotiana benthamiana . Overexpression of AhRRS5 significantly enhanced the resistance of heterogeneous tobacco to R. solanacearum, with diverse resistance levels in different transgenic lines. Several defence‐responsive marker genes in hypersensitive response, including SA, JA and ET signals, were considerably up‐regulated in the transgenic lines as compared with the wild type inoculated with R. solanacearum . Nonexpressor of pathogenesis‐related gene 1 ( NPR1 ) and non‐race‐specific disease resistance 1 were also up‐regulated in response to the pathogen. These results indicate that AhRRS5 participates in the defence response to R. solanacearum through the crosstalk of multiple signalling pathways and the involvement of NPR1 and R gene signals for its resistance. This study may guide the resistance enhancement of peanut and other economic crops to bacterial wilt disease.